Analisis Yuridis Terhadap Pengalihan Aset Ruko Atas Pembina Yayasan Medica Dengan Cara Jual Beli ( Studi Putusan Nomor : 21/Pid.B/2021/Pn.Bnj) - Jitro Sembiring, Ronan; Rizki (Universitas Ekasakti, 2023)
In Indonesia, foundations are regulated by law number 28 of 2004. In this regulation, it is clearly stated that foundations have their own assets and rights, which are not owned by their management. Prior to the existence of the law on foundations, the existence of foundation assets often caused controversy because sometimes foundations, which should aim for the benefit of society, were misused to commit illegal acts. In some cases, land and assets of foundations are even traded illegally, which of course violates the law and the property rights of the foundations itself. The research conducted in this study is normative research, where law is the basic reference in research. In terms of the problem in this study, the transferred foundation assets, namely a shophouse located on Jalan Veteran, Binjai District, Binjai City. The assets belong to the Medica Foundation but are in the name of Dr.Reinhard Silalahi, who in this case is the Trustee of the Foundation and the Defendant in the case in Decision No. 21/Pid.B/2021/Pn.Bnj. Based on the provisions of the Article 28 In the law on Foundation, Trustee are organs of the Foundation which have authority that is not granted to management or the supervisors by this law or the articles of association. In the verdict of the panel of judges, they argued that where was no act of fraud commited by the defendant, such as using a false name, false dignity, deception, and a series of lies. However, this act is considered as an unlawful act in the civil realm.